Reactive wetting between molten Al alloy and ceramic particles - Kevorkijan, Varužan (Kovine zlitine tehnologije, 1998)
In this paper, the linear time dependence and the exponential temperature of the volume fraction of ceramic reinforcement immersed in the matrix was addressed theoretically. Applying the same theoretical approach to the dynamics of the reactive infiltration of molten aluminum into porous ceramic preform, the parabolic relation between the infiltration length and time as well as the exponential relation between the infiltration length and temperature were also derived. It was demonstrated that the rate of reactive wetting and the dynamics of reactive infiltration of molten aluminum into porous ceramic perform depend on the exergonic nature of the interfacial reaction, the kinetis of the interfacial chemistry involved and the efficiency of the system in using the energy released by the interfacial chemical reaction for the formation of new surface in the melt.
Keywords: ceramic; keramika; aluminijeve zlitine; aluminium alloy; kompoziti; fizika površin; energija; omakanje